DEVELOPING COMMUNICATIVE COMPETENCE OF PRIMARY SCHOOL STUDENTS THROUGH INTERACTIVE GAMES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This research explores the effectiveness of game-based learning in enhancing young learners’ English communicative competence. The research emphasizes that modern language education focuses on using language in real-life contexts rather than solely learning grammar or vocabulary. Grounded in theories of communicative competence (Hymes, Canale, Swain) and child development (Vygotsky, Piaget, Dewey), the study demonstrates that interactive games—such as role-plays, storytelling, and cooperative tasks—improve speaking skills, motivation, confidence, teamwork, and social interaction among primary school students.